2008
DOI: 10.1177/112067210801800605
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Stem Cells Transplantation in the Reconstruction of the Ocular Surface: 6 Years Experience

Abstract: Significantly better long-term outcomes were achieved with autotransplantation of the limbus compared with allogeneic limbal grafts from living-related and cadaveric donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…10 Of those receiving CLAU transplantation, ocular surface remained stable in 61.9% of the patients after 6 years. 19 Our study showed a similar trend. However, the rates of 58.9% ± 8.5% at 2 years, 51.1% ± 9.0% at 5 years, and 39.3% ± 9.2% at 7 years were much higher than the previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…10 Of those receiving CLAU transplantation, ocular surface remained stable in 61.9% of the patients after 6 years. 19 Our study showed a similar trend. However, the rates of 58.9% ± 8.5% at 2 years, 51.1% ± 9.0% at 5 years, and 39.3% ± 9.2% at 7 years were much higher than the previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Lang and coauthors [24], has described these as preoperative risk factors for transplant failure; The encouraging aspect of these cases is that despite being considered as a "failure", all these patients experienced improvement of preoperative visual acuity. Our results are very similar to those found by others authors, where failure rate after the transplant has been reported between 6 and 50% [9][10][11][12][13][14][15][16]. In addition, the present technique proved to be safe, since 100% of donor's eyes presented adequate healing and no complications in the donor eye.…”
Section: Discussionsupporting
confidence: 80%
“…Regenerative treatment with stem cells has had a breakthrough in medicine in recent years [5] and the specialty of ophthalmology has not been left behind; the international literature has demonstrated the effectiveness of limbal stem cell transplantation in the treatment of corneal neovascularization [9][10][11][12][13][14][15]; however, there are few studies reporting long term results of this procedure in combination with amniotic membrane use. Corneal neovascularization is characterized by a vascularization of the corneal epithelium, chronic inflammation, epithelial defects, photophobia and loss of vision, leading to blindness where corneal transplants are ineffective because the limbal niche induces corneal rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-8 However, despite promising success rates, significant failure rates at long-term follow-up beyond 2 years, because of both KLAL failure and isolated keratoplasty failure, have been noted. [9][10][11] Solomon et al 9 reported an overall survival of ambulatory vision of only 53.6% at 3 years in their patient cohort, whereas Ilari and Daya 10 reported only 33% graft survival at 3 years in their patient cohort. For this growing population of patients with severe ocular surface disease who have failed PKP after KLAL, evidence to guide subsequent treatment decisions is absolutely critical.…”
mentioning
confidence: 93%